2007
DOI: 10.1007/s10832-007-9352-7
|View full text |Cite
|
Sign up to set email alerts
|

Charge storage at the Pt/YSZ interface

Abstract: The electrochemical behavior of Pt/YSZ electrodes in oxygen containing atmosphere at 450°C has been investigated by double-step chronoamperometry and programmed linear sweep cyclic voltammetry. The response of the O 2 (g),Pt/YSZ system in these experiments could be separated into a time dependent and a steady state contribution, the former being dominated by pseudocapacitive processes. It is proposed that Pt-O type species were stored via different processes at three different locations in the O 2 (g),Pt/YSZ s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 12 publications
2
19
0
Order By: Relevance
“…Electrochemical characterization of the Pt/YSZ electrode was made using chronoamperometry [10,11] and linear sweep voltammetry [9]- [11] in O 2 -containing atmosphere.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochemical characterization of the Pt/YSZ electrode was made using chronoamperometry [10,11] and linear sweep voltammetry [9]- [11] in O 2 -containing atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, recent studies are reviewed on the phenomenon of P-EPOC with Pt/YSZ catalyst combining reaction rate measurements in ethylene combustion [8] and electrochemical analysis [9]- [11], aiming at getting a deeper insight to the origin of P-EPOC.…”
Section: Introductionmentioning
confidence: 99%
“…The Pt/YSZ electrode was first characterized by electrochemical methods using chronoamperometry [8,9] and linear sweep voltammetry [8][9][10] in O 2 -containing atmosphere at 450°C. Then, used as catalyst and electrode at the same time, the catalytic activity of Pt deposited onto …”
Section: Resultsmentioning
confidence: 99%
“…For a better understanding, a series of techniques such as single and double step chronoamperometry, chronocoulometry and programmed cyclic voltammetry were performed as reported in [22]. They indicated that application of an anodic polarization on the Pt/YSZ system caused short and long term oxygen storage in the working electrode.…”
Section: Discussionmentioning
confidence: 99%